2018
DOI: 10.1155/2018/8478240
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of TiO2/SiO2 Monoliths as Photocatalysts on Methanol Oxidation

Abstract: Photocatalytic materials based on silica-titania (SiO2-TiO2) were synthesized by sol-gel and dip-coating method. TEOS and titanium butoxide were used as precursors of the silica-titania, respectively. A thin film with anatase phase was obtained on the surface of the support. The effect of variables as dispersion mechanism, immersion time, and number of treatment cycles were studied. The materials were characterized using X-ray diffraction, scanning electron microscopy, energy dispersion scanning, and N2 adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Nano sized TiO2 can be synthesized by various techniques like Sol-gel, Sputtering, Combustion flame, and thermal plasma etc. [5] The purpose of adding amorphous SiO2 was because of its mechanical characteristics, superior adsorption capacity, and high surface area [6].…”
Section: Introductionmentioning
confidence: 99%
“…Nano sized TiO2 can be synthesized by various techniques like Sol-gel, Sputtering, Combustion flame, and thermal plasma etc. [5] The purpose of adding amorphous SiO2 was because of its mechanical characteristics, superior adsorption capacity, and high surface area [6].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, pristine or doped TiO 2 NPs have been immobilized on metal oxides, carbon nanotubes, reduced graphene oxide, glassy substrates, polymeric surfaces and silica [32][33][34]. Previous works have shown that particularly the employment of silica (SiO 2 ) as the support increased the specific surface area of the catalyst, restricted the agglomeration of TiO 2 NPs and suppressed the anatase-to-rutile phase transformation during synthesis [35][36][37][38][39][40]. The use of silica is also regarded as a "safe-by-design" approach to prevent the release of TiO 2 NPs into the environment due to strong Si-O-Ti interactions [41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%